Evaluating GOTO Investment Strategies After Major Investor Exit: DiD Approach - Hernawati, Cindy; Prijadi, Ruslan (Jurnal Akuntansi, Keuangan, dan Manajemen, 2025)
Purpose: This study tests whether strategic divestment by prominent investors affects the valuation of firms that keep stakes in a high-growth, volatile company, PT?GoTo Gojek Tokopedia?Tbk?(GOTO). Methodology/approach: A difference-in-differences design compares market performance before and after SoftBank and Alibaba’s exits. Firms retaining GOTO PT?Telkom Indonesia?Tbk?(TLKM) and PT?Astra International?Tbk?(ASII) form the treatment group, while matched non-holders serve as controls. Graphical and statistical checks confirmed parallel trends, validating the model. Results/findings: Continued GOTO ownership after divestment reduces Tobin’s?Q by 0.291 (p?=?0.093). The Average Treatment Effect on the Treated shows a significant 20.459 point drop in firm value post-event (p?<?0.001). Thus, markets penalized exposure to GOTO, consistent with the signaling hypothesis that major investor exits convey adverse information. Conclusion: Retaining equity in a volatile firm after high-profile departures poses valuation and reputational risks. Negative market reactions suggest skepticism about GOTO’s prospects and heightened the perceived risk for remaining shareholders. Therefore, the timing and extent of post-divestment exposure warrant careful strategic consideration. Limitations: The treatment sample is small (two firms), macro sectoral factors are excluded, and data end in Q2?2024, limiting long term inference. Contribution: By linking ownership signals to firm value in an emerging market context, this study enriches the literature on divestment, signaling, and corporate strategy, demonstrating tangible market costs for stakeholders who remain invested after influential exits.